Toward the Search for New Photosensitizers for Dsscs: Theoretical Study of Both Substituted Zn(Ii) and Si(Iv) Phthalocyanines - Cardenas-Jiron, G; Zambrano-Angulo, M (Royal Society of Chemistry, 2024)
We report a density functional theory (DFT) study performed for a set of 66 compounds based on zinc(ii) and silicon(iv) phthalocyanines (Pcs) with potential applications in dye-sensitized solar cells (DSSCs). The effect of the metal center (Zn, Si), periplanar and axial substituents, and anchor groups like anhydrous, carboxyl, and catechol on the electronic, optical, photovoltaics, and adsorption properties is investigated. Using the TD-DFT methodology and M06 and CAM-B3LYP functionals, we calculated the absorption spectra on optimized structures and in the solution phase but not on structures relaxed in the solvent. We obtained a strong Q band and a weak Soret band in the UV-Vis region, which are attributed to the transitions of type π-π* as described by the Gouterman orbitals. Q bands calculated show absorption up to 667 nm for ZnPcs and up to 769 nm for SiPcs, suggesting an essential role of the metal atom. The systems have a bathochromic effect in the order of secondary amine > primary amine > hydroxyl > amide > ester. We also found that the anhydrous and carboxyl groups favor absorption at longer wavelengths than the catechol group. The ZnPc systems show a slightly larger electron injection ΔGinj (∼1.1 eV) than SiPcs (∼0.9 eV), with similar values for the three anchor groups. The interaction energies (Eint) between ZnPcs/SiPcs and TiO2 in molecular and periodic configuration and corrected by the counterpoise method indicate that SiPcs predict more negative values than ZnPcs. The anchor group effect is relevant; the carboxyl moiety leads to stronger interactions than the anhydrous moiety. The strategies used could help to identify new photosensitizers for DSSCs. © 2024 The Royal Society of Chemistry.